Music therapy, knowledge of music and architecture: the effect of music on grief caused by mourning in Ilam Chamri religion - Karami, Peyman; Zolfagharzadeh, Hassan; Sameh, Reza (Social Determinants of Health, 2022)
Background: The art of music and architecture are one of the most visible manifestations of culture and ethnicity in every historical period, and music has historically played a valuable role in softening human perception and spirits; thus, can play a decisive role in health life for a long time. Methods: Non-pharmacological therapies, have the potential to supplement medical treatment alternatives to aid recovery and well-being in health care. Music therapy is a relatively new discipline of musicology that has lately been able to assist individuals in the treatment of ailments that are inextricably linked to architecture. Is it possible for music and architecture, which have an unbreakable link with the past, to retain this bond and build a relationship of abuse and violation with the science of psychology and counselling? Results: This essay was written in a combined-analytical (comparative, descriptive, and analytical) style, using data collected via documentary, library, and field research approaches. The findings of this study reveal that music and architecture may have a similar effect on the human psyche, and the science of music therapy has been able to capitalize on these similarities in medicine. Conclusion: The current article first introduces the commonalities of music and architecture and expresses the importance of these two arts’ commonalities, after which it will be addressed how these commonalities in an ancient ritual called Chamri, which is held in Ilam province.